2012
DOI: 10.2165/11635490-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Ten Years of Experience with Biphasic Insulin Aspart 30

Abstract: Biphasic insulin aspart 30 (BIAsp 30) includes 30% soluble rapid-acting insulin aspart (IAsp) along with an intermediate-acting 70% protaminated IAsp that provides coverage of prandial and basal insulin in a single injection. As BIAsp 30 has been available internationally for 10 years, this review provides a comprehensive overview of the discovery of BIAsp 30, its pharmacokinetic and pharmacodynamic profile, safety and efficacy outcomes from the clinical trial programme, ‘real-life’ clinical insights provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 105 publications
(127 reference statements)
0
16
0
1
Order By: Relevance
“…BIAsp 30 comprises 30% soluble rapid-acting insulin aspart (IAsp; prandial component) and 70% intermediate-acting crystallized protamine-complexed IAsp (basal component). [ 30 ] BIAsp 50 and BIAsp 70 are available for patients who require more prandial insulin; however, these formulations are not the focus of this review. BIAsp 30 is a well-established T2D treatment, available since 2002, which is associated with a wealth of clinical data from RCTs and observational studies of its efficacy and safety compared with other oral glucose-lowering therapies in a diverse range of patient populations.…”
Section: B Iphasic I Nsulin a mentioning
confidence: 99%
“…BIAsp 30 comprises 30% soluble rapid-acting insulin aspart (IAsp; prandial component) and 70% intermediate-acting crystallized protamine-complexed IAsp (basal component). [ 30 ] BIAsp 50 and BIAsp 70 are available for patients who require more prandial insulin; however, these formulations are not the focus of this review. BIAsp 30 is a well-established T2D treatment, available since 2002, which is associated with a wealth of clinical data from RCTs and observational studies of its efficacy and safety compared with other oral glucose-lowering therapies in a diverse range of patient populations.…”
Section: B Iphasic I Nsulin a mentioning
confidence: 99%
“…An extensive clinical dataset, based on numerous randomized clinical trials and real-life observational studies, supports the efficacy and good safety profiles of BIAsp 30 and lispro mix 25 in the initiation and intensification of insulin therapy; these data have been reviewed [ 10 , 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Biphasic insulin aspart 30 (BIAsp 30) was launched internationally in 2002, with the primary advantage of offering the possibility of effectively controlling both postprandial and fasting blood glucose levels with a single, convenient drug while also having the pharmacokinetic (PK) and pharmacodynamic (PD) advantages of an analog-based insulin formulation for people with type 2 diabetes mellitus (T2DM). In 2012, after 10 years of use of BIAsp 30 in millions of patients worldwide, a review co-written by two of the present authors (Liebl, Mohan) described its discovery, structure, PK, and PD and summarized clinical efficacy and safety data, primarily from randomized trials [ 1 ]. That review concluded that BIAsp 30 administered once daily (OD) or twice daily (BID) was appropriate for insulin initiation and was a good option for patients wishing to switch from biphasic human insulin (BHI 30).…”
Section: Introductionmentioning
confidence: 99%